Artikel tata tertib kelas di MTs Khaudlul Ulum - aprilia anggin cahyani (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2022)
Abstract Student discipline in the classroom is an effort to build the character of student discipline. However, in general the rules are made not too heeded the students so that gradually affect the efforts to improve the quality of Education. This study aims to find the problem of why students are not enthusiastic about their own discipline and then find a solution partispatif with students. The study was conducted at MTs Khaudul Ulum Penajung. The study used an action approach with steps in the form of SWOT analysis, finding problems related to the implementation of student discipline, discussing together the solution, drawing up a solution action plan, organizing to socialize it, then carrying out joint action,and finally reflection evaluating together also for further improvement. The parties involved are the head of the madrasah, deputy head of Student Affairs, the Student Council builders, and student council managers. The management theory used is the theory of plan-do-check-act (PDCA). The results of this action research are: (a)the finding of priority issues stemming from the lack of discipline of students in the Classroom, (b)planned participatory joint action on the manufacture of student rules, (c)The Division of tasks and socialization, (d)the holding of Joint Action for the manufacture of student rules, and (e) reflection to evaluate the implementation of the action. Recommendations/ suggestions: (a)this action activity is developed continuously, and (b)further actions are more directed to the purpose of improving the quality of madrasah. Keywords: action research, quality improvement, student discipline